The Effectiveness of the Read-Aloud Method on Reading Fluency Among Fourth-Grade Elementary School Students - Alamsyah, Alamsyah; Priyadi, Antonius Totok; Halidjah, Siti (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study aimed to examine the effectiveness of the read-aloud method in improving the reading fluency of fourth-grade students at SD Negeri 24 Ani Senabah, Sejangkung Subdistrict, Sambas Regency, West Kalimantan. The study employed a quantitative approach using a one-group pretest-posttest quasi-experimental design. The research subjects consisted of all 26 fourth-grade students selected through total sampling. Data were collected through pretest and posttest read-aloud performance assessments measuring three aspects of reading fluency: accuracy, fluency, and prosody. The instrument used a 1–4 scale rubric validated by two Indonesian language education experts and demonstrated good reliability (Cronbach’s Alpha = 0.82). The treatment was conducted in four learning sessions involving teacher modeling, student read-aloud practice, and corrective feedback. Data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, paired sample t-test, and Cohen’s d effect size analysis with the assistance of SPSS software. The results showed an increase in the mean score from 58.60 to 78.60 after the intervention, with a statistically significant difference between pretest and posttest scores (p < 0.05). The findings indicate that the read-aloud method is effective in improving students’ reading fluency and can serve as an alternative instructional strategy to strengthen elementary students’ literacy skills, particularly in prosodic reading aspects that support overall reading comprehension.